How is circadian preference associated with cyber-victimization? A moderated mediation model of hostile recognition and online self-disclosure in Chinese early adolescent students - Jia, Yanru; Wu, Yuntena; Jin, Tonglin; Zhang, Lu (Frontiers in Psychology, 2022)
Although circadian preference is widely accepted to be a critical factor in improving one's negative experience, little is known about how this association cyber-victimization. The current study sought to examine whether the Eveningness was significantly related to adolescents’ negative experiences. We further examined its in-victimization events and whether hostile recognition and online self-disclosure played a vital role in the Eveningness and adolescents’ cyber-victimization. The participants included 583 adolescents from four middle schools in China who completed the questionnaires regarding their experience with the Eveningness, cyber-victimization, hostile recognition, and online self-disclosure. Results indicated that adolescents with a high level of the Eveningness were likely to experience cyber-victimization. Hostile recognition significantly mediated the relationship between the Eveningness and adolescents’ cyber-victimization. Furthermore, online disinhibition moderated the indirect relationship between the Eveningness and cyber-victimization. Specifically, the paths from the Eveningness to hostile recognition and from hostile recognition to cyber-victimization became strengthened when adolescents experienced high levels of online disinhibition. The results further imply that researchers should pay more attention to remote factors, such as circadian preference, and their relationship with cyber-victimization, so as to help them adapt to school requirements and reduce the frequency of victimization.